Life-satisfaction and Selected Personality Traits of Teachers in Elementary Schools - Pugnerová, Michaela; Kvintová, Jana (e-Pedagogium, 2008)
This presentation focuses on the life satisfaction of teachers in elementary schools from two regions in the Czech Republic. The purpose of the research was to examine not only the overall life satisfaction of teachers but also the factors that may influence it. We focused on selected personality traits (extraversion, neuroticism) and their association with the overall life satisfaction of teachers. This is a part of a larger research program that evaluates the well-being of teachers in elementary schools.
Keywords: Extraversion; neuroticism; overall life satisfaction; factors influencing life satisfaction